2008
DOI: 10.1103/physrevc.78.044901
|View full text |Cite
|
Sign up to set email alerts
|

Fully integrated transport approach to heavy ion reactions with an intermediate hydrodynamic stage

Abstract: We present a coupled Boltzmann and hydrodynamics approach to relativistic heavy ion reactions. This hybrid approach is based on the Ultra-relativistic Quantum Molecular Dynamics (UrQMD) transport approach with an intermediate hydrodynamical evolution for the hot and dense stage of the collision. Event-by-event fluctuations are directly taken into account via the non-equilibrium initial conditions generated by the initial collisions and string fragmentations in the microscopic UrQMD model. After a (3+1)-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
418
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 402 publications
(441 citation statements)
references
References 124 publications
(122 reference statements)
14
418
0
Order By: Relevance
“…On the other hand it has been shown that thermal models consistently describe the production yields of hadrons (and nuclei [49]) very well. We can therefore assume thermal production of clusters from a fluid dynamical description to heavy ion collisions [50,51]. Figures 1 and 2 show the results for di-baryon and hypernuclei yields in the mid-rapidity region of central, b < 3.4 fm, heavy ion collisions at different beam energies.…”
Section: Hypernucleimentioning
confidence: 99%
“…On the other hand it has been shown that thermal models consistently describe the production yields of hadrons (and nuclei [49]) very well. We can therefore assume thermal production of clusters from a fluid dynamical description to heavy ion collisions [50,51]. Figures 1 and 2 show the results for di-baryon and hypernuclei yields in the mid-rapidity region of central, b < 3.4 fm, heavy ion collisions at different beam energies.…”
Section: Hypernucleimentioning
confidence: 99%
“…For previous studies of resonances within this model see [14][15][16][17][18][19][20][21][22][23] the UrQMD model the reader is referred to [26,27]. Recent development concerning the inclusion of a hydrodynamic phase are described in [28]. Experimentally, the reconstruction of resonances is challenging.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Recently, H. Petersen et al has updated the UrQMD code to include hydrodynamics [26] and made it publicly available. The hydrodynamics included in the original version (UrQMD v. 3.3p1) is a 3+1D ideal hydrodynamic simulation in the Cartesian coordinate system with the simple freeze-out surface determined at a constant t. MUSIC on the other hand uses the hyperbolic coordinate system and generates a fairly complicated iso-thermal freeze-out surface.…”
Section: Urqmd Afterburnermentioning
confidence: 99%